Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Certainly! To solve the given equation:
[tex]\[ x - 3\sqrt{x} - 18 = 0 \][/tex]
we can use a substitution method. Let's set [tex]\( u = \sqrt{x} \)[/tex]. Then, we know that [tex]\( u^2 = x \)[/tex]. Substituting [tex]\( u \)[/tex] for [tex]\( \sqrt{x} \)[/tex], the equation becomes:
[tex]\[ u^2 - 3u - 18 = 0 \][/tex]
This is now a quadratic equation in terms of [tex]\( u \)[/tex]. The general form of a quadratic equation is:
[tex]\[ au^2 + bu + c = 0 \][/tex]
where, in our case, [tex]\( a = 1 \)[/tex], [tex]\( b = -3 \)[/tex], and [tex]\( c = -18 \)[/tex].
To solve this quadratic equation, we'll use the quadratic formula, which is:
[tex]\[ u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Plugging in our values ([tex]\( a = 1 \)[/tex], [tex]\( b = -3 \)[/tex], [tex]\( c = -18 \)[/tex]):
1. Calculate the discriminant:
[tex]\[ \text{Discriminant} = b^2 - 4ac \][/tex]
[tex]\[ \text{Discriminant} = (-3)^2 - 4(1)(-18) \][/tex]
[tex]\[ \text{Discriminant} = 9 + 72 \][/tex]
[tex]\[ \text{Discriminant} = 81 \][/tex]
2. Substitute the values into the quadratic formula:
[tex]\[ u = \frac{-(-3) \pm \sqrt{81}}{2 \cdot 1} \][/tex]
[tex]\[ u = \frac{3 \pm 9}{2} \][/tex]
3. Solve for [tex]\( u \)[/tex]:
[tex]\[ u_1 = \frac{3 + 9}{2} = \frac{12}{2} = 6 \][/tex]
[tex]\[ u_2 = \frac{3 - 9}{2} = \frac{-6}{2} = -3 \][/tex]
Since [tex]\( u = \sqrt{x} \)[/tex] and [tex]\( \sqrt{x} \)[/tex] cannot be a negative number, we discard the solution [tex]\( u = -3 \)[/tex], as it does not give a real value for [tex]\( x \)[/tex].
4. Now, using the valid solution [tex]\( u = 6 \)[/tex]:
[tex]\[ \sqrt{x} = 6 \][/tex]
Squaring both sides, we get:
[tex]\[ x = 6^2 = 36 \][/tex]
Therefore, the solution to the equation [tex]\( x - 3\sqrt{x} - 18 = 0 \)[/tex] is:
[tex]\[ x = 36 \][/tex]
Additionally, other value is also derived for [tex]\(\sqrt(x) = -3 \)[/tex], thus giving
[tex]\[ x = (-3)^2 = 9 \][/tex]
and the solutions are:
\[ x = 36 \text{ and }x = 9]
[tex]\[ x - 3\sqrt{x} - 18 = 0 \][/tex]
we can use a substitution method. Let's set [tex]\( u = \sqrt{x} \)[/tex]. Then, we know that [tex]\( u^2 = x \)[/tex]. Substituting [tex]\( u \)[/tex] for [tex]\( \sqrt{x} \)[/tex], the equation becomes:
[tex]\[ u^2 - 3u - 18 = 0 \][/tex]
This is now a quadratic equation in terms of [tex]\( u \)[/tex]. The general form of a quadratic equation is:
[tex]\[ au^2 + bu + c = 0 \][/tex]
where, in our case, [tex]\( a = 1 \)[/tex], [tex]\( b = -3 \)[/tex], and [tex]\( c = -18 \)[/tex].
To solve this quadratic equation, we'll use the quadratic formula, which is:
[tex]\[ u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Plugging in our values ([tex]\( a = 1 \)[/tex], [tex]\( b = -3 \)[/tex], [tex]\( c = -18 \)[/tex]):
1. Calculate the discriminant:
[tex]\[ \text{Discriminant} = b^2 - 4ac \][/tex]
[tex]\[ \text{Discriminant} = (-3)^2 - 4(1)(-18) \][/tex]
[tex]\[ \text{Discriminant} = 9 + 72 \][/tex]
[tex]\[ \text{Discriminant} = 81 \][/tex]
2. Substitute the values into the quadratic formula:
[tex]\[ u = \frac{-(-3) \pm \sqrt{81}}{2 \cdot 1} \][/tex]
[tex]\[ u = \frac{3 \pm 9}{2} \][/tex]
3. Solve for [tex]\( u \)[/tex]:
[tex]\[ u_1 = \frac{3 + 9}{2} = \frac{12}{2} = 6 \][/tex]
[tex]\[ u_2 = \frac{3 - 9}{2} = \frac{-6}{2} = -3 \][/tex]
Since [tex]\( u = \sqrt{x} \)[/tex] and [tex]\( \sqrt{x} \)[/tex] cannot be a negative number, we discard the solution [tex]\( u = -3 \)[/tex], as it does not give a real value for [tex]\( x \)[/tex].
4. Now, using the valid solution [tex]\( u = 6 \)[/tex]:
[tex]\[ \sqrt{x} = 6 \][/tex]
Squaring both sides, we get:
[tex]\[ x = 6^2 = 36 \][/tex]
Therefore, the solution to the equation [tex]\( x - 3\sqrt{x} - 18 = 0 \)[/tex] is:
[tex]\[ x = 36 \][/tex]
Additionally, other value is also derived for [tex]\(\sqrt(x) = -3 \)[/tex], thus giving
[tex]\[ x = (-3)^2 = 9 \][/tex]
and the solutions are:
\[ x = 36 \text{ and }x = 9]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.